KINERJA LABEL UNTUK MEMPREDIKSI UMUR SIMPAN PEMPEK PADA BERBAGAI KONDISI PENYIMPANAN - Melati Pratama, Endang Warsiki, dan Liesbetini Haditjaroko (Jurnal Teknologi Industri Pertanian, 2016)
Pempek is food that contains 18.26% protein. It is a very good medium to bacteria growth mainlyStaphylococcus aureus. The deterioration of pempek during storage due to S. aureus could be detected by thecolour change of phenol red indicator. It was made in the label form and it was attached in the inside of plasticpackaging. The treatments was treated by the conditions of the packaging (non vacuumed, vacuumed), thetemperature of storage (5-10oC for cold temperature, 30-32oC for room temperature). The result showed theconditions of packaging did not affect the change of label colour, while temperature storage affected it. Thechange of label colour was from red to yellow. The colour change of label in two conditions package (nonvacuumed and vacuumed) were stored at room temperature for time storage of 8th hours, while at coldtemperature for time storage of 24th hours. The colour change of label to yellow was showed by increasing ofohue on the label. The increase was caused by increasing acidity of the label due to S. aureus growth. Thedecreasing of pH label from 7.43 to 7.33. Amount of S. aureus on the label and pempek increased from 0 to0.19×103 cfu/g and from 0.03 to 0.54×103 cfu/g.Keywords: phenol red indicator label, S.aureus, pempek